Hié̂n pháp : Nước Việt Nam dân chủ cộng hòa (Vietnamese law coll. (Harvard Law School), 1982)
Compilation of various materials including typescript articles on the Constitution of Vietnam, National Assembly gathered in December 22-27, 1975, and partial copies of newspaper articles.